Immune Reconstitution in the Aging Host: Opportunities for Mechanism-Based Therapy in Allogeneic Hematopoietic Cell Transplantation - Lin, Richard J.; Elias, Harold K.; van den Brink, Marcel R. M. (Frontiers in Immunology, 2021)
Older patients with hematologic malignancies are increasingly considered for allogeneic hematopoietic cell transplantation with encouraging outcomes. While aging-related thymic dysfunction remains a major obstacle to optimal and timely immune reconstitution post- transplantation, recent accumulating evidence has suggested that various aging hallmarks such as cellular senescence, inflamm-aging, and hematopoietic stem cell exhaustion, could also impact immune reconstitution post-transplantation in both thymic-dependent and independent manner. Here we review molecular and cellular aspects of immune senescence and immune rejuvenation related to allogeneic hematopoietic cell transplantation among older patients and discuss potential strategies for mechanism-based therapeutic intervention.